Frequent Pet Contact as Risk Factor for Allergic Bronchopulmonary Aspergillosis in Cystic Fibrosis - Grehn, Claudia; Eschenhagen, Patience; Temming, Svenja; Düesberg, Uta; Neumann, Konrad; Schwarz, Carsten (Frontiers in Cellular and Infection Microbiology, 2021)
Aspergillus fumigatus (Af) frequently colonizes the respiratory tract of patients with cystic fibrosis (CF). Af is associated with loss of pulmonary function and allergic bronchopulmonary aspergillosis (ABPA), a hypersensitivity fungal lung disease. Environmental factors have impact on CF patients’ lung function variation. The aim of this nationwide questionnaire survey was to investigate the amount of CF patients with frequent pet contact including pet species and to examine the potential impact of frequent pet contact on the occurrence of Af colonization and ABPA diagnosis in these patients. The survey was carried out in 31 German CF centers in 2018. A total of 1232 who completed the surveys were included, and statistical analysis was performed by chi-squared test. Within the study cohort 49.8% of subjects (n = 614; CF patients < 18years: 49.4%, n = 234; ≥ 18years: 50.1%, n = 380) reported frequent contact to pets, of which 60.7% reported frequent contact to dogs, 42.3% to cats and other animals. Of those with frequent pet contact, 71.8% (n = 441) had contact to one pet or more pets from the same family. Af colonization was not significantly associated with frequent pet contact. ABPA diagnosis was documented in 16.7% (n = 206) of all included CF patients and was significantly associated with frequent pet contact (18.9%, n = 116, p = 0.042), confirming previous single center examinations. Particularly, patients with frequent contact to dogs showed an increased ABPA prevalence of 21.3%. Frequent pet contact might be a risk factor for ABPA. CF patients who are sensitized to Af should be informed about the increased risk to develop an ABPA by frequent pet contact. Patients with recurrent onset of ABPA should be evaluated in terms of frequent pet contact.